Institutions of education, then and today : the legacy of German idealism - Cobben, Paul. (Critical Studies in German Idealism, 2010)
The theme of "Institutions of Education: then and today" not only corresponds with the basic questions raised in German Idealism, but is also central to the question of whether it is legitimate to study German Idealism in our era. Elaborating on this project immediately raises the problem of institutional differentiation, which characterizes multicultural society. Does the variety of educational institutions not, by definition, exclude the shared conception and realization of adulthood that is presupposed by German Idealism? This book shows that German Idealism can still participate in the contemporary debate on education: it is not only helpful in raising relevant questions, but can also be transformed into positions which can deal with the pluriformity that characterizes contemporary society.